Mechanical behavior and related microstructural aspects of a nano-lamellar TiAl alloy at elevated temperatures. (15th April 2017) - Klein, T.; Usategui, L.; Rashkova, B.; Nó, M.L.; San Juan, J.; Clemens, H.; Mayer, S.
Abstract: Advanced intermetallic γ -TiAl based alloys, which solidify via the disordered β phase, such as the TNM + alloy, are considered as most promising candidates for structural applications at high temperatures in aero and automotive industries, where they are applied increasingly. Particularly creep resistant microstructures required for high-temperature application, i.e. fine fully lamellar microstructures, can be attained via two-step heat-treatments. Thereby, an increasing creep resistance is observed with decreasing lamellar interface spacing. Once lamellar structures reach nano-scaled dimensions, deformation mechanisms are altered dramatically. Hence, this study deals with a detailed characterization of the elevated temperature deformation phenomena prevailing in nano-lamellar TiAl alloys by the use of tensile creep experiments and mechanical spectroscopy. Upon creep exposure, microstructural changes occur in the lamellar structure, which are analyzed by the comparative utilization of X-ray diffraction, scanning and transmission electron microscopy as well as atom probe tomography. Creep activation parameters determined by mechanical characterization suggest the dominance of dislocation climb by a jog-pair formation process. The dislocations involved in deformation are, in nano-lamellar TiAl alloys, situated at the lamellar interfaces. During creep exposure the precipitation of β o phase and ζ -silicide particles is observed emanating from the α 2 phase, which is due to the accumulation of Mo and Si at lamellar interfaces. Graphical abstract: Image 1